Tourism stakeholders' perspective of sustainable practices at Kinabalu Park / Leezora Bathsheba Benjamin ... [et al.] - Benjamin, Leezora Bathsheba; Abdul Kadir, Sitti Lelah Rabiah; Mohd Fuza, Zatul Iffah; Wan Kamarudin, Wan Nor Bayah; Wan Nawawi, Wan Nazriah (Universiti Teknologi MARA, Sabah, 2021)
Over the years, many people have gradually shown a higher preference for nature-based ecotourism, partly because of the increased awareness of the importance of sustainable tourism. Issues regarding international travel limitation and the need for social distancing due to the COVID-19 pandemic have diverted local tourists' attractions to turn to more nature-based ecotourism rather than crowded city tours. Premier ecotourism destinations usually adopt sustainable management practices such as good visitors and risk management with regular training and capacity building. This study aims to examine the perception of stakeholders (in this case, the government sector) towards sustainable tourism in Kinabalu Park, with an emphasis on sustainable practices. Synchronous qualitative interviews with the stakeholders were conducted online and thematic analysis were done via the NVIVO software. The findings showed that the government agencies managing Kinabalu Park clearly understood sustainable tourism. The findings provide valuable information.